Associations of alcohol use, mental health and socioeconomic status in England: Findings from a representative population survey. (1st February 2021) - Puddephatt, Jo-Anne; Jones, Andrew; Gage, Suzanne H.; Fear, Nicola T.; Field, Matt; McManus, Sally; McBride, Orla; Goodwin, Laura
Highlights: Mental health problems and alcohol misuse were associated, specifically more severe mental health problems. Strong associations were found between having a severe mental health problem and non-drinking. Socioeconomic characteristics did not account for these relationships. Abstract: Background: Alcohol use and mental health problems often co-occur, however, little is known about how this varies by type of mental health problem and to what extent associations are explained by socioeconomic status (SES). Our study examined the prevalence and associations of non-drinking, hazardous use, and harmful/probable dependence in individuals who do and do not meet criteria for different mental health problems and whether associations remained after adjustment for SES. Methods: A secondary analysis of an English dataset, 2014 Adult Psychiatric Morbidity Survey ( N = 7, 218), was conducted. The Alcohol Use Disorder Identification Test was used to categorise participants as non-drinking, low risk, hazardous use and harmful/probable dependence. Mental health problems were screened using a range of validated tools. Multinomial logistic regression analyses were used to address study aims. Results: The prevalence of non-drinking, hazardous and harmful/probable dependence was higher among those meeting criteria for a mental health problem. After adjustment for SES, non-drinking was most common in those meeting criteria for probable psychotic disorder (MOR = 3.42, 95 %CI = 1.74–6.70), hazardous use in those meeting criteria for anti-social personality disorder (MOR = 2.66, 95 %CI = 1.69–4.20) and harmful/probable dependence in those meeting criteria for borderline personality disorder (MOR = 9.77, 95 % CI = 4.81–19.84). Conclusions: There were marked increases in the odds of reporting both non-drinking and harmful drinking among those meeting criteria for a mental health problem, particularly more severe problems. Our findings indicate that the relationship between alcohol and mental health is more complex and comorbid alcohol and mental health problems should be treated in parallel with access to both services.